Synthesis and Crystal Structure of A Binuclear Zinc(II) Complex - Guo, Ya-Ning (Asian Journal of Chemistry, 2011)
A new binuclear complex Zn2L2ClN3 1 (HL = 2-(1pyridin-2-yl-ethylideneamino)- phenol) has been synthesized and characterized by X-ray single-crystal diffraction analysis. The complex crystallizes in orthorhombic, space group Pbca with a = 13.9620(15) Å, b = 8.7547(11) Å, c = 20.441(2) Å, V = 2498.5(5) Å3, Z = 4, C26H22N7O2ClZn2, Mr = 630.70, Dc = 1.677 g cm-3, F(000) = 1280, μ = 2.067 mm-1, the final R = 0.0681 and wR = 0.1535 for 1292 observed reflections with I > 2s(I). The coordination geometry of each Zn(II) atom is trigonal bipyramidal and the two Zn(II) ions are bridged by two phenolic oxygen atoms with Zn…Zn separation of 3.172 Å. The present complex of zinc(II) exhibits a three-dimensional structure through hydrogen bondings and the conformation and packing is also stabilized by them.